Menuju Hukum Islam yang Inklusif-Humanistis: Analisis Pemikiran Jasser Auda tentang Maqāṣid Al- Sharī‘ah - Muhammad Salahuddin (Ulumuna, 2012)
Methodological debates in the study of maqāṣid al-sharī‘ah presented several variants of polarization, as doctrinaire-normative-deductive and historical-empirical-inductive. This paper aims to probe carefully the theory of meaning the maqāṣid al-sharī‘ah offered by Jasser Auda. It was found that Auda’s offer come from his observation on the failure of Islamic law to reconstruct the values embodied in authoritative texts (Qur’an, Sunnah) which are compatible with the social, economical, and political development of modern society. Implementation of maqāṣid al-sharī‘ah must be paralleled with maqāṣid al-mukallaf, so that Islamic sharī‘ah in its humanist face in accordance with its mission as raḥmah li al-‘alamīn can be realized.